OPTIMALISASI PENULISAN KARYA TULIS ILMIAH PADA GURU SD NEGERI JETIS 2 YOGYAKARTA - Trisniawati - Trisniawati; Kristi Wardani; Dinar Martia Azizah (ABDIMAS DEWANTARA, 2018)
The optimization scientific paper writing activities for the teachers of Jetis 2 Public Elementary School Yogyakarta is aimed to optimize the paper writing skills of the Jetis 2 Public Elementary School Yogyakarta teachers on the elementary scientific journal. This activity was held in November. The first activity is the introduction of the scientific papers types and how to write a scientific paper properly and correctly. The second activity is the writing of the scientific paper on the Taman Cendekia journal. The third activity is the guidance of the articles written by the teachers. The fourth activity is Scientific Paper Writing Workshop of the Jetis 2 Public Elementary School Yogyakarta teachers. Those activities run well and gain its success, which is attended by 9 teachers of Jetis 2 Public Elementary School Yogyakarta. The result of this activity is in the form of scientific articles, which are made by Jetis 2 Public Elementary School Yogyakarta which is reaching 2 numbers of articles subsequently published on the Taman Cendekia journal.Keywords:Â optimization, scientific paper, journal.